A SYSTEMATIC APPROACH TOWORDS ACHIEVING EQUILIBRIUM IN WORK LIFE OF TEACHERS (International Journal of Food and Nutritional Sciences, 2022)
Purpose: It has become difficult for people in many professions, especially teachers, to strike a balance between their home and professional duties. It is crucial to understand how professionals balance (if at all they balance) their professional and family obligations because work-life balance for teachers is a fairly broad topic that discusses both career development and family care on opposite sides. This study intends to measure teachers' levels of work-life balance as well as the many institutional strategies used to help instructors strike a balance between their personal and professional lives. This study discovered that the majority of instructors struggled at work with a sense of life being missed, and the institutions did nothing to help them. The study is conducted only among the teaching staff in the town of Murudeshwar.Design:The design is to conduct the research using a questionnaire and a survey to understand how people feel their stress and work in general.Finding Result: Most of the Women teachers are satisfied and have a better work-life balance, when compared to men in general as their total family income is less when compared to women teachers.Originality/ Value: The paper is original and has a value for further research in this directionPaper type: Empirical research for understanding and making clear to have a better work life balance in life.